Mathematical modeling of the quasi-stationary processes of viscous mixture mixing in a rectangual area by the R-functions method - Gybkina, Nadiia Valentynivna; Sidorov, Maxim Viktorovich; Stadnikova, Hanna Viktorіvna (Національний технічний університет "Харківський політехнічний інститут", 2022)
Mixing processes are found in the chemical, pharmaceutical and food industries. Fluid mixing is one of the fundamental scientific problems associated with modern concepts of regular and chaotic dynamics. The paper considers the problem of mathematical modeling of the quasi-stationary process of mixing a viscous mixture. This problem consists of two sub-problems: determination of the velocity field in the flow region (Eulerian formalism) and investigation of the trajectories of individual fluid particles (Lagrange formalism). To solve the first subproblem, it is proposed to jointly use the principle of superposition, the structural method (method of R-functions) and the Ritz variational method. The methods of nonlinear dynamics and qualitative theory of differential equations are used to solve the second subproblem. A plane quasi-steady flow is considered in a rectangular region and it is assumed that the side walls are at rest, and the upper and lower walls move alternately according to the given laws. According to the method of R-functions, the structures of the solutions were built and the use of the Ritz variational method for the approximation of the uncertain components of the structures was justified. The operation of the proposed method is illustrated by the results of a computational experiment, which was conducted for different modes of wall motion. The practical interest of the considered regimes is due to the fact that they lead to the emergence of chaotic behavior when mixing occurs most efficiently. Using the methods of nonlinear dynamics, the location of periodic (hyperbolic and elliptical) points was investigated and the Poincaré section was constructed. Further research with the help of the method proposed in the work can be related to the consideration of flows in more geometrically complex regions and more complex mixing regimes, as well as in the application to the calculation of industrial problems.

Процеси перемішування зустрічаються в хімічній, фармацевтичній та харчовій промисловостях. Перемішування рідини є однією з фундаментальних наукових проблем, пов’язаних з сучасними концепціями регулярної та хаотичної динаміки. У роботі розглянуто задачу математичного моделювання квазістаціонарного процесу перемішування в’язкої суміші. Ця задача складається з двох підзадач: визначення поля швидкостей в області течії (формалізм Ейлера) та дослідження траєкторій окремих частинок рідини (формалізм Лагранжа). Для розв’язання першої підзадачі пропонується сумісно використати принцип суперпозиції, структурний метод (метод R-функцій) та варіаційний метод Рітца. Для розв’язання другої підзадачі використовуються методи нелінійної динаміки та якісної теорії диференціальних рівнянь. Плоска квазістаціонарна течія розглядається в прямокутній області і вважається, що бічні стінки перебувають у стані спокою, а верхня та нижня стінки рухаються по черзі за заданими законами. Відповідно до методу R-функцій побудовано структури розв’язків та обґрунтовано застосування для апроксимації невизначених компонент структур варіаційний метод Рітца. Роботу запропонованого методу проілюстровано результатами обчислювального експерименту, який було проведено для різних режимів руху стінок. Прикладний інтерес розглянутих режимів обумовлений тим, що вони призводять до виникнення хаотичної поведінки, коли перемішування відбувається найбільш ефективно. Методами нелінійної динаміки досліджено розташування періодичних (гіперболічних та еліптичних) точок та побудовано переріз Пуанкаре. Подальші дослідження за допомогою запропонованого у роботі методу можуть бути пов’язані з розглядом течій у більш геометрично складних областях та більш складних режимів перемішування, а також у застосуванні до розрахунку промислових задач.
Математичне моделювання квазістаціонарних прпоцесів перемішування в'язкої суміші у прямокутній області методом R-функцій
Keywords: viscous fluid quasi-stationary flow; mixing flow; stream function; R-functions method; Ritz method; periodic points; квазістаціонарна течія в'язкої рідини; перемішування; функція течії; метод R-функцій; метод Рітца; періодичні точки